Comprehensive review of implications of COVID‐19 on clinical outcomes of cancer patients and management of solid tumors during the pandemic. (20th October 2020) - Madan, Ankit; Siglin, Joshua; Khan, Aleem
Abstract: Coronavirus disease‐2019 (COVID‐19) has emerged as a novel infection which has spread rapidly across the globe and currently presents a grave threat to the health of vulnerable patient populations like those with malignancy, elderly, and immunocompromised. Healthcare systems across the world are grappling with the detrimental impact of this pandemic while learning about this novel disease and concurrently developing vaccines, strategies to mitigate its spread, and treat those infected. Cancer patients today face with a unique situation. They are susceptible to severe clinically adverse events and higher mortality from COVID‐19 infection as well as morbidity and mortality from their underlying malignancy. Conclusion: Our review suggests increased risk of mortality and serious clinical events from COVID‐19 infection in cancer patients. However, risk of adverse events does not seem to be increased by cancer therapies. True impact of COVID‐19 on cancer patients will unravel over the next few months. We have also reviewed clinical features of COVID‐19, recent recommendations from various medical, surgical, and radiation oncology societies for major solid tumor types like lung, breast, colorectal, and prostate cancer during the duration of this pandemic. Abstract : Our review details the effects of COVID‐19 on clinical outcomes in cancer patients across different continents. COVID‐19 has been associated with higher fatality rate among cancer patients but cancer treatments have not been shown to increase the risk of mortality. We have reviewed the changes recommended in the management of lung, breast, colorectal, and prostate cancer during the duration of the pandemic.